History and the configuration of the educational cartographic heritage of the Alfonso VIII Secondary School of Cuenca - Serrano Gil, Óscar; Requena, Jesús López Requena (Historia y Memoria de la Educación, 2021)
The teaching of geography has required the use of maps as an important tool in learning how to represent the Earth. Educational institutions have configured a scarcely known but interesting and rich cartographic heritage over time. This work shows the origin of the collection, the methodology, and the presentation of the cartographic resources contained in the map library of the Alfonso VIII Secondary Education Institute of Cuenca. This map collection was created at the end of the 19th century. It brings together more than two hundred reproductions from different places (France, Italy, Germany, Austria, Switzerland, and Argentina). Wall maps used widely in teaching-learning processes prevail. Although maps are used much less today, their reevaluation can contribute the historical legacy based on values of heritage education.